An integrated online-to-offline model for HIV post-exposure prophylaxis (O2O-PEP) scale-up among men who have sex with men (MSM): Protocol for developing a pilot randomized controlled trial - Luo, Qianqian; Luo, Yongchuan; Li, Tianying; Cui, Tianyu (Frontiers in Public Health, 2022)
Background HIV post-exposure prophylaxis (PEP) is an evidence-based biomedical HIV prevention strategy consisting of a 28-day course of highly active antiretroviral therapy after recent potential exposure to HIV. However, awareness and uptake of PEP among men who have sex with men (MSM) are very low. Innovative and effective methods are needed to support PEP implementation among MSM. This work reports a protocol to design and evaluate an online-to-offline-based delivery model for HIV PEP uptake (O2O-PEP) in Chinese MSM. Methods and analysis This will be a two-phase study. In phase 1, we will develop an O2O-PEP model delivered through the WeChat mini-app (an app built into the WeChat platform). The O2O-PEP model initially includes four core components: a gamification-based education package for PEP, an online HIV risk assessment tool, a free online booking system for PEP initiation, and offline PEP prescription in the study hospitals. In phase 2, a two-arm pilot stratified randomized controlled trial comparing the O2O-PEP group with the standard care group will be designed to assess the feasibility, usability, and preliminary evidence of the efficacy of the O2O-PEP model in increasing PEP uptake among Chinese MSM. Model feasibility and usability will be further explored for broader model implementation. Discussion The O2O-PEP model is one of the first interventions in China aiming to promote PEP initiation in Chinese MSM. Components in the O2O-PEP model could assist MSM in better understanding their HIV infection risk and increasing accessibility of PEP. Moreover, coupled with online and offline recruitment, the O2O-PEP model has great potential to reach and engage MSM who are not involved in care by traditional methods. Clinical trial registration No. ChiCTR2200062538.